Scale development and psychometric properties of the Cardiac Self-Blame Attributions scale in patients with cardiovascular disease. Issue 2 (July 2018) - Harry, Kadie M; Bennett, Kymberley K; Marszalek, Jacob M; Eways, Kalon R; Clark, Jillian MR; Smith, Andrew J; Waters, Marcia; Bergland, Dennis; Umhoefer, Amanda; Wilson, Elizabeth J
Patients with cardiovascular disease may attribute their cardiovascular disease to their behaviors (behavioral self-blame) or to their dispositions (characterological self-blame). However, findings are mixed on the effects of behavioral self-blame and characterological self-blame on health outcomes, possibly because there are no validated, multiple-item measures. This study developed and tested an 11-item Cardiac Self-Blame Attributions scale via questionnaire data from 121 patients with cardiovascular disease. Results yielded a two-factor structure that explained 65 percent of the variance, with good reliability and discriminant validity. Findings suggest that the scale is reliable and valid and can be used to understand the cardiac attributions patients create.